Soil and terrain database for Southern Africa (Food and Agriculture Organization of the United Nations, 2003)
Contains the Soil and Terrain Database (SOTERSAF) for eight countries in southern Africa. Additional soil information and maps for selected countries are also included. The scale of the maps varies betwen 1:1 million and 1:2.5 million